Ethnobotanical study of antihypertensive medicinal plants in Sari Makmur Village, West Kalimantan, Indonesia - RUQIAH GANDA PUTRI PANJAITAN; ANANDA DWI PUTRI; EKO SRI WAHYUNI; KURNIA NINGSIH; TITIN TITIN; DONA FITRIAWAN; LIANGYUE LIANGYUE (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Panjaitan RGP, Putri AD, Wahyuni ES, Ningsih K, Titin, Fitriawan D, Liangyue. 2025. Ethnobotanical study of antihypertensive medicinal plants in Sari Makmur Village, West Kalimantan, Indonesia. Biodiversitas 26: 3356-3366. Hypertension is one of the leading causes of death worldwide, often going undetected due to its non-communicable yet fatal nature. One non-pharmacological treatment for hypertension is herbal therapy using medicinal plants. This study aims to inventory medicinal plants used to treat hypertension by the Malay community in Sari Makmur Village, Tekarang Sub-district, Sambas District, West Kalimantan, Indonesia. The research employed a qualitative descriptive method with a data triangulation technique, including interviews, observations, documentation, and the creation of a herbarium for plant identification involving five informants. The results show that there are 12 plant species used as antihypertensives by the community of Sari Makmur Village, including bunga panyok (Catharanthus roseus), daun sop (Apium graveolens), engkudu (Morinda citrifolia), gerinang (Averrhoa bilimbi), kumis kucing (Orthosiphon aristatus), mahkota dewa (Phaleria macrocarpa), nangka belande (Annona muricata), patterwali (Tinospora cordifolia), pegage (Centella asiatica), salam (Syzygium polyanthum), sambung nyawe (Gynura procumbens), and telang (Clitoria ternatea). The species most frequently mentioned by informants for treating hypertension were nangka belande (A. muricata) and salam (S. polyanthum) while the most used plant family was Apiaceae. The most utilized plant part was the leaf, and the most frequent method of preparation was boiling. These findings highlight the importance of preserving and supporting local conservation efforts as an alternative resource in the development of herbal medicines to ensure their sustainability.